Evaluation of the outcome of myringoplasty in active versus inactive chronic otitis media without cholesteatoma - Ridha, Firdaws F.; Khefi, Raed A.; Alwan, Muhanned M. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Myringoplasty is a procedure used to seal(reconstruct) a perforated tympanic membrane using a graft material by underlay or overlay techniques . Temporalis fascia is the commonly used graft material. Aim of study: to evaluate the difference in outcome of myringoplasty in cases of active and inactive chronic otitis media without cholesteatoma. Patients and Methods: a prospective study of 54 cases of myringoplasty in adult age group whom age ranges from (20-40 years) and the duration of the disease ranges from (6-24 months). All patients were complaining of chronic otitis media without cholesteatoma assessed clinically, audiologically and radiologically, all cases operated under general anesthesia and temporalis fascia grafting (underlay technique) via post-auricular incision. Results: twenty six (48.2%) patients had an active chronic otitis media without cholesteatoma while the remaining twenty eight (51.8%) patients had an inactive chronic otitis media without cholesteatoma those with an active disease 21 (80.8%) cases have successful closure of the perforation while in those 28 cases with an inactive disease 24 (85.7%) cases have successful closure of the perforation. Factors of gender, age, side of the perforation, duration of the perforation, and the pre-operative management for the active ears had no significant effect on the outcome of myringoplasty, P values = 0.5, 0.1, 0.9, 0.5, 0.6, 0.6 and 0.7 respectively which are > 0.05. The overall percentage of success of grafting was 83.3% and the failure of grafting was 16.7%. Conclusion:- The activity of the middle ear (infection) has little impact on the success rate of closure of tympanic membrane perforation.